An optical neural chip for implementing complex-valued neural network - H. Zhang (Nature Portfolio, 2021)
Most demonstrations of optical neural networks for computing have been so far limited to real-valued frameworks. Here, the authors implement complex-valued operations in an optical neural chip that integrates input preparation, weight multiplication and output generation within a single device.